2008
DOI: 10.1111/j.1365-2923.2008.03111.x
|View full text |Cite
|
Sign up to set email alerts
|

CanMEDS evaluation in Canadian postgraduate training programmes: tools used and programme director satisfaction

Abstract: This study demonstrates that Canadian postgraduate training programmes use a variety of assessment tools to evaluate the CanMEDS competencies. Programme directors are neutral or concerned about how the CanMEDS roles other than that of Medical Expert are evaluated in their programmes. Further efforts are required to establish best practice in CanMEDS evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 15 publications
3
105
0
6
Order By: Relevance
“…Concurrent validity testing with other tools, such as OSCEs and DECs, assessing clinical competence outlined by the CanMEDs roles is also warranted in EM and other training programs. 3,9 Although the use of an ITER may allow for the evaluation of the intrinsic domains such as the Health Advocate and Collaborator roles, which have been regarded as extraneous in EM compared to the Medical Expert, Communicator, and Professional roles, further exploration into the situational factors that affect clinical performance is also needed. From a measurement point of view, it is more feasible to measure scenarios and participants in isolation than to decipher their interactions according to Lurie, who states, ''Descriptions of 'competencies' should thus specify the range of examinees and situations to which they apply.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrent validity testing with other tools, such as OSCEs and DECs, assessing clinical competence outlined by the CanMEDs roles is also warranted in EM and other training programs. 3,9 Although the use of an ITER may allow for the evaluation of the intrinsic domains such as the Health Advocate and Collaborator roles, which have been regarded as extraneous in EM compared to the Medical Expert, Communicator, and Professional roles, further exploration into the situational factors that affect clinical performance is also needed. From a measurement point of view, it is more feasible to measure scenarios and participants in isolation than to decipher their interactions according to Lurie, who states, ''Descriptions of 'competencies' should thus specify the range of examinees and situations to which they apply.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of program directors showed concern about how the non-Medical Expert or intrinsic CanMEDS roles are evaluated in postgraduate medical education programs. 3 Although the use of multiple tools may be recommended when assessing the CanMEDS roles, the utility and feasibility of such a task within resident training curricula needs further investigation. As Lurie suggests, 4 the use of multiple and different assessment methods need to be based on the comparability of these measures as a function of whether the performance measured represents a stable characteristic of the examinee rather than unique elements derived from prescriptive testing situations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of Canadian residency programs demonstrated an average of 1.75 assessment methods. 5 Of equal importance is the frequency and consistency of formative assessment, 6 its integration into the educational curriculum, and the "catalytic effect" 7 of assessment results and feedback on improving individual performance. The selection of assessment methods will be based at least in part on the availability of financial, faculty, and learning resources within a residency.…”
Section: Overview Of Assessment Methods Identifiedmentioning
confidence: 99%
“…Residents may have limited experience dealing with these less common scenarios, and the CanMEDS OSCE provides a direct assessment method for these specific competencies. Interestingly, in a survey of residency program directors from across Canada, it was revealed that they were least satisfied with the assessment of the Health Advocate Role (Chou, et al, 2008). This further highlights the potential utility of the CanMEDS OSCE as examiners can control case content to specifically and directly evaluate Roles that may not necessarily occur on a regular basis during day-to-day practice.…”
Section: Discussionmentioning
confidence: 99%